El aprendizaje basado en problemas para el desarrollo de habilidades científicas en los estudiantes de cuarto y quinto año de Educación General Básica de la Unidad Educativa Isabel la Católica en el cantón Guaranda, provincia Bolívar el periodo 2024- 2025. - Alava Peñaloza, Keila Saray (2025)
The research project titled Problem-based Learning for Developing Scientific Skills in the Fourth and Fifth-year Students of Basic General Education of the Isabel la Católica Educational Unit in the Bolívar-Cantón Guaranda Province. Its objective was to contribute to developing scientific skills in students through Problem-Based Learning. The methodology adopted a mixed approach, which is considered essential to obtain a deeper and more detailed understanding. The results were obtained through data collection techniques such as the structured interview and the estimation scale. These techniques have facilitated an in-depth evaluation of the impact of the strategy used, providing valuable information. In conclusion, Problem-Based Learning is an effective methodology for developing scientific skills in students. Because, by addressing real-world problems, students become protagonists of their education, connecting meaningfully with scientific concepts. This contributes to children's academic and professional future, facilitating learning that transcends the simple retention of information.